Species of aphids found in ornamental and wild plants in Pagar Alam District, South Sumatra, Indonesia - CHANDRA IRSAN; ERISE ANGGRAINI; WENNY RAMADHANI (Society for Indonesian Biodiversity, 2023)
Abstract. Irsan C, Anggraini E, Ramadhani W. 2023. Species of aphids found in ornamental and wild plants in Pagar Alam District, South Sumatra, Indonesia. Biodiversitas 24: 6602-6612. Aphids are one of the crucial pests in tropical and sub-tropical regions. The presence of aphids in a plant can be very detrimental due to their role as vectors. Aphids exhibit species diversity, but not much information has been reported about the species diversity of aphids associated with essential crops such as ornamental plants. Furthermore, many aphid species, such as wild plants, were found on plants that were not hosts. Therefore, this study reported the species of aphids found in ornamental and wild plants. The field research employed purposive and direct observation to inventory cultivated or wild plants hosting and collecting aphids. The plant selection process included cultivated plants encompassing ornamental plants and wild plants or weeds. The collection and identification of host plants and aphids involved systematic searches for the selected plants and subsequent examination for the presence of aphids. Observations were made to all existing plant species to find those colonized by aphids. This study revealed that a total of 15 species of aphids were found in Ornamental plants, Aphis craccivora Koch, 1854, Aphis spiraecola Patch, 1914, Aphis glycines Matsumura, 1917, Aphis gossypii Glover, 1877, Aulacorthum solani Kaltenbach, 1843, Macrosiphoniella sanborni Gillette, 1908, Macrosiphum rosae Linnaeus, 1758, Myzus persicae Sulzer, 1776, Neomyzus circumflexus Buckton, 1876, Pentalonia caladii van der Goot, 1917, Rhopalosiphum nymphaeae Linnaeus, 1761, Sinemegoura citricola van der Goot, 1917, Toxoptera aurantii Boyer de Fonscolombe, 1841, Toxoptera citricidus Kirkaldy, 1907, Toxoptera odinae van der Goot, 1917 and the total of 11 species aphids found in weeds, A. gossypii, A. craccivora, A. glycines, A. citricola, Greenidea sp., Hystroneura setariae Thomas, 1878, Hiperomyzus sp., Lipaphis erysimi Kaltenbach, 1843, Rhopalosiphum maidis Fitch, 1856, Rhopalosiphum padi Linnaeus, 1758, Schizaphis rotundiventris Signoret, 1860.